2018
DOI: 10.1002/14651858.cd008735.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroids for infants with biliary atresia following Kasai portoenterostomy

Abstract: Background Biliary atresia is a life-threatening disease characterised by progressive destruction of both intra-and extra-hepatic biliary ducts. The mainstay of treatment is Kasai portoenterostomy, as soon as the disease has been confirmed. Glucocorticosteroids are steroid hormones which act on the glucocorticoid receptor and have a range of metabolic and immunomodulatory effects. Glucocorticosteroids are used to improve the postoperative outcomes in infants who have undergone Kasai portoenterostomy. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Age at HPE has been investigated mainly from the viewpoint of SNL and clearance of jaundice: 57 to 90% of patients undergoing HPE within 60 days of life will have a successful reestablishment of bile flow 45 ; as a result SNL appears to be improved. 46 Impact on perioperative complications has not been clearly analyzed. Our study found the absence of correlation between age at HPE and perioperative complications.…”
Section: Factors Associated With Complicationsmentioning
confidence: 99%
“…Age at HPE has been investigated mainly from the viewpoint of SNL and clearance of jaundice: 57 to 90% of patients undergoing HPE within 60 days of life will have a successful reestablishment of bile flow 45 ; as a result SNL appears to be improved. 46 Impact on perioperative complications has not been clearly analyzed. Our study found the absence of correlation between age at HPE and perioperative complications.…”
Section: Factors Associated With Complicationsmentioning
confidence: 99%
“…Treatment with adjuvant steroids after KPE has previously been used to assist restoring bile flow and anti-inflammation; however, the effects of steroids on BA outcome remain controversial (35,36). In several studies, no benefits of postoperative steroids on prognosis were observed (36,37), whereas other studies showed that treatment with adjuvant steroids after KPE may improve short-term (≤1 year) JC. In this study, our results revealed that patients treated with adjuvant steroids initially suffered from no postoperative bile drainage and also had a higher risk obtaining a low 2-years NLS (HR = 1.992, 95% CI = 1.419-2.797, P = 0.000).…”
Section: Correction Of Coagulation and Protection Of Blood Vessels Canmentioning
confidence: 99%
“…Thus far, no post-HPE adjuvant therapy has been shown to change outcomes in BA. Several trials showed that prednisone treatment after HPE did not promote improved bile drainage and caused significant adverse effects 26, 39, 40 . Another trial showed that IVIG administration was similarly ineffective at promoting bile drainage post-HPE 27 .…”
Section: Clinical Managementmentioning
confidence: 99%